Aracy de Almeida: samba e malandragem no Brasil dos anos 1930 e 1940 - Oliveira, Vitor Hugo de (2018)
Production of a radio documentary on the life of Aracy de Almeida, a samba singer consecrated in the 1930s and 1940s. Aracy was the eldest, and only woman, of four brothers, in the family of Mr. Baltazar and Dona Hermogênea. In the neighborhood of the Encantado began by singing religious hymns in the protestant cults that frequented on Sundays. Later, when he met Noel Rosa, he started performing on the radio. As a young woman, he played pool, cursed, and accompanied Noel in wandering around the corners where he liked to circulate, including the Mangue. Talented with her nasal voice, she sang in the best nightclubs and worst birocks in Rio de Janeiro. The interpreter is mentioned among the female singers of the radio although she was a constant companion of the malandragem and the famous samba wheels of the neighborhood of Lapa. As a friend of intellectuals, Aracy lived in the 1930s and 1940s an unusual life for most of the women of that time who were, as a rule, relegated to household chores, dedicated to the family and subdued by the state apparatus. The artist in the 1950s disintegrated from the great interpreter who had been and resurfaced, already in the television age, as a jury of freshmen program, displaying a caricature image, which did not even remember the glorious past that had lived.